Intention to use e-payments from the perspective of the unified theory of acceptance and use of technology (UTAUT): Evidence from Yemen - Fahd Alduais; Mohammad O. Al-Smadi (Economies, 2022)
This study explores the challenges facing the current e-payment systems and investigates the main factors that support using the e-payment system. This study used a cross-sectional approach. An online survey was conducted on Yemeni consumers as part of the collection of data. The data from 486 questionnaires were analyzed using smartPLS4 and Jamovi software for structural model analysis and statistical analysis. According to the PLS-SEM results, the structural model shows that R2 is 0.757, which explains the variances in behavioral intention via all the constructs. Statistically, the intention to use e-payment systems is significantly and positively influenced by performance and effort expectancies and social influence. In contrast, facilitation conditions are significantly and negatively correlated with behavioral intention. This is attributed to consumers' view of the infrastructure of Internet services, which does not contribute to the behavioral intention and acceptance of using electronic payment in Yemen. Contrary to expectations, age does not moderate the relationship between performance expectancy, social influence, and intention to use e-payment systems; hence, the related hypothesis was not supported. This study provides valuable suggestions for policymakers, designers, developers, and researchers, enabling them to better understand the critical aspects of using the electronic payment system. This study developed a model for predicting the likelihood of acceptance of electronic payments in a country that has not given adequate attention to this issue. An application and evaluation of the UTAUT model in Yemen are presented in this study.
Keywords: 330; e-payment; facilitating conditions; intention; technology acceptance; Yemen